Legality Aspect Of Conducting Documents Only Arbitration In Indonesia - Wiko, Garuda; Kinanti, Fatma Muthia (Universitas Negeri Gorontalo, 2021)
Documents-Only Arbitration (DOA) is a type of arbitration that is carried out entirely by written documents-only. DOA is beneficial when the burden and substance of the dispute are relatively simple and when there are obstacles to conduct a face-to-face proceeding (instance in the Covid-19 Pandemic or limitation of cost). This study examined the DOA trial method and how it is based on Law No. 30 Year1999 concerning Arbitration and Alternative Dispute Resolution as the lex arbitri in Indonesia. Regulations, Rules, and Procedures from arbitration institutions, both national and international are also studied to better understand the problem. This study aimed to explain the legality of arbitration based on Documents-Only Arbitration in Indonesia. This study concluded that the conduct of DOA is very possible to be implemented in Indonesia and does not conflict with Law No. 30 Year 1999 concerning Arbitration and Alternative Dispute Resolution (Arbitration Law).